Large anomalous transverse transport properties in atomically thin 2D Fe3GaTe2 - Brahim Marfoua; Jisang Hong (NPG Asia Materials)
Abstract Anomalous transverse conductivities, such as anomalous Hall conductivity (AHC), anomalous Nernst conductivity (ANC), and anomalous thermal Hall conductivity (ATHC), play a crucial role in the emerging field of spintronics. Motivated by the recent fabrication of two-dimensional (2D) ferromagnetic thin film Fe3GaTe2, we investigate the thickness-dependent anomalous transverse conductivities of the 2D Fe3GaTe2 system (from one to four layers). The atomically ultrathin 2D Fe3GaTe2 system shows above-room-temperature ferromagnetism with a large perpendicular magnetic anisotropy energy. Furthermore, we obtain a large AHC of −485 S/cm in the four-layer thickness, and this is further enhanced to −550 S/cm with small electron doping. This AHC is seven times larger than the measured AHC in thicker 2D Fe3GaTe2 (178 nm). The ANC also reaches 0.55 A/K.m in the four-layer structure. Along with these, the four-layer system exhibits a large ATHC (−0.105 ~ −0.135 W/K.m). This ATHC is comparable to the large ATHC found in Weyl semimetal Co3Sn2S2. Based on our results, the atomically ultrathin 2D Fe3GaTe2 system shows outstanding anomalous transverse conductivities and can be utilized as a potential platform for future spintronics and spin caloritronic device applications.